2018
DOI: 10.1002/ajpa.23724
|View full text |Cite
|
Sign up to set email alerts
|

Geophagy among nonhuman primates: A systematic review of current knowledge and suggestions for future directions

Abstract: ObjectivesGeophagy, the intentional consumption of earth, is widely practiced among humans and other mammals, but its causes are not well understood. Given the growing number of reports of geophagy among nonhuman primates (NHP), we sought to (1) advance and codify our understanding of the patterns and functional and evolutionary significance of geophagy among NHP and (2) provide a research agenda for a more unified approach to its study.MethodsWe systematically reviewed all available literature on NHP geophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 196 publications
0
38
0
1
Order By: Relevance
“…Some bird and mammalian species, including elephants, macaques, tamarins, gorillas, chimpanzees, and humans (Wilson ), consume soil of a variety of kinds, often in the form of clay. Geophagy is widespread and has been observed on all continents inhabited by humans and nonhuman primates (Pebsworth, Huffman, Lambert, & Young, ), with archeological evidence suggesting its practice to be as old as 2 million years (Clark, ). Though the most prominent causes of geophagy remain unclear (Pebsworth et al, ), the practice of geophagy increases micronutrient intake, which may have nutritional value, and other benefits such as the detoxification of harmful compounds such as alkaloids in the diet (Klaus, Klaus‐Hugi, & Schmid, ), protection against infection by parasites and pathogens (Knezevich ), and alleviation of gastro‐intestinal upsets (Mahaney, Hancock, Aufreiter, & Huffman, ; Young ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some bird and mammalian species, including elephants, macaques, tamarins, gorillas, chimpanzees, and humans (Wilson ), consume soil of a variety of kinds, often in the form of clay. Geophagy is widespread and has been observed on all continents inhabited by humans and nonhuman primates (Pebsworth, Huffman, Lambert, & Young, ), with archeological evidence suggesting its practice to be as old as 2 million years (Clark, ). Though the most prominent causes of geophagy remain unclear (Pebsworth et al, ), the practice of geophagy increases micronutrient intake, which may have nutritional value, and other benefits such as the detoxification of harmful compounds such as alkaloids in the diet (Klaus, Klaus‐Hugi, & Schmid, ), protection against infection by parasites and pathogens (Knezevich ), and alleviation of gastro‐intestinal upsets (Mahaney, Hancock, Aufreiter, & Huffman, ; Young ).…”
Section: Introductionmentioning
confidence: 99%
“…Geophagy is widespread and has been observed on all continents inhabited by humans and nonhuman primates (Pebsworth, Huffman, Lambert, & Young, ), with archeological evidence suggesting its practice to be as old as 2 million years (Clark, ). Though the most prominent causes of geophagy remain unclear (Pebsworth et al, ), the practice of geophagy increases micronutrient intake, which may have nutritional value, and other benefits such as the detoxification of harmful compounds such as alkaloids in the diet (Klaus, Klaus‐Hugi, & Schmid, ), protection against infection by parasites and pathogens (Knezevich ), and alleviation of gastro‐intestinal upsets (Mahaney, Hancock, Aufreiter, & Huffman, ; Young ). As pointed out by Pebsworth et al (), in a review of the literature in this field, the total elemental composition of soil may not reflect the amount of minerals available for the consumer, and in vitro studies are needed to determine bioavailability of mineral elements eaten in the course of geophagy (Pebsworth et al, ; Seim et al, ; Wilson ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among wild primates, geophagy has been well‐studied in Neotropical primates (Ferrari, Veiga & Urbani, ; Izawa, ), Old World monkeys (Mahaney, Milner & Sanmugadas, ; Oates, ; Wakibara et al., ), and great apes (Mahaney, Hancock, Aufreiter & Huffman, ; Mahaney, Hancock, Aufreiter, Milner & Voros, ; Mahaney, Watts & Hancock, ), but remains poorly studied in Madagascar's lemurs (but see Ganzhorn, ; Norscia, Carrai, Ceccanti & Borgognini Tarli, ; Semel, ). A recent review on primate geophagy by Pebsworth, Huffman, Lambert and Young () found 44 studies describing lemur geophagy, of which only five directly analyzed consumed soils. While most researchers agree that geophagy is typically an adaptive behavior, causes for geophagy remain poorly understood (Krishnamani & Mahaney, ; Pebsworth et al., ).…”
Section: Introductionmentioning
confidence: 99%